Motor Nerve Conduction Tests in Carpal Tunnel Syndrome - Kristel M. Kasius (Frontiers in Neurology, 2019)
Background: For the preoperatively often required confirmation of clinically defined carpal tunnel syndrome (CTS), sensory as well as motor nerve conduction studies can be applied. The aim of this study was to test the sensitivity of specific motor nerve conduction tests in comparison with, as well as in addition to, sensory nerve conduction tests.Methods: In 162 patients with clinically defined CTS, sensory and motor nerve conduction tests were performed prospectively. Sensitivity and specificity of all tests were computed. Also, Receiver Operating Characteristic (ROC) analyses were conducted.Results: Sensitivity for all sensory tests was at least 79.4% (DIG1). All tests had a specificity of at least 95.7%. The motor conduction test with the highest sensitivity was the TLI-APB (81.3%); its specificity was 97.9%.Conclusion: In the electrophysiological confirmation of CTS, sensory nerve conduction tests and terminal latency index have a high sensitivity. If, however, sensory nerve action potentials cannot be recorded, all motor nerve conduction tests have a high sensitivity.